Agripreneurship and Poverty Reduction: Empirical Evidence from Tubah Sub-Division, North West Region, Cameroon - Akumbom, Paul; Egwu, Mary Juliet Bime; SHILLIE, Peter NGEK (Finance & Economics Review, 2023)
Purpose: The purpose of the study is to investigate how entrepreneurship in the agriculture sector could help alleviate poverty in the Tubah region of Cameroon. Specifically, the study seeks to explore the potential of agripreneurship in creating job opportunities, increasing income levels, and improving the living standards of people in the region. Methods: Mixed-method design was employed for the study. Data was gathered with the help of a structured questionnaire from 384 households in Tubah-Cameroon and analyzed using the partial least square. Results: Results revealed that attitudes towards agripreneurship, innovative behavior, and the need for achievement had a positive effect on poverty reduction in Tubah Sub-Division. Inheritance of family ventures and start-up motives were found to exert negative effect on poverty reduction. Implications: The study is expected to contribute to the understanding of how entrepreneurship in the agriculture sector can be leveraged to promote economic opportunities and promote sustainable development in rural areas.